Scenarios of future Land use/Land cover changes: impacts on cropland use in Šiauliai region (Lithuania) - Gomes, Eduardo (2022)
Agricultural systems supply a wide range of ecosystem services. Projecting future agricultural land-use changes is key to anticipating the potential impacts of human activities. In this work, we assessed future agricultural land-use changes, using the Dinamica-EGO platform, under three scenarios: A0-(business-as-usual), A1- (sustainable agriculture), and A2-(agricultural intensification) for 2040 in the Šiauliai region (Lithuania). Spatial autocorrelation was evaluated by using a Moran’s I index and the spatial patterns with the Getis analysis and landscape metrics. The results showed that croplands will increase 29.6% in the A0, 14.95% in the A1, and 29.63% in the A3 scenario. According to the Getis results, cold spots are in the surrounding of Šiauliai city, and hot spots in the northeast of the Šiauliai region. It was verified a high cropland fragmentation in A1 and low fragmentation in A0 and A2 scenarios. These results are critical for land management to understand cropland impacts under different scenarios.